Chaotic behavior in the pseudoinverse control of redundant and hyper-redundant robots - Duarte, Fernando B. M. (2019)
Several kinematic control algorithms for redundant manipulators adopt generalized inverse matrices. In this line of thought, the generalized inverse control scheme is tested through experiments that reveal the difficulties that often arise. The experiments confirm the non-linear and chaotic performance of the algorithm and give a deeper insigth towards the future development of superior trajectory control systems.